2017
DOI: 10.1136/bjsports-2016-096458
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to increase adherence to therapeutic exercise in older adults with low back pain and/or hip/knee osteoarthritis: a systematic review and meta-analysis

Abstract: Meta-analysis provides moderate-quality evidence that booster sessions with a physiotherapist assisted people with hip/knee osteoarthritis to better adhere to therapeutic exercise. Individual high-quality trials supported the use of motivational strategies in people with chronic low back pain and behavioural graded exercise in people with osteoarthritis to improve adherence to exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
154
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(171 citation statements)
references
References 55 publications
4
154
1
1
Order By: Relevance
“…Adherence interventions that target multiple behavior change techniques have been suggested to improve compliance. Patient specific interventions to improve exercise motivation and reduce barriers to exercise may increase adherence to the exercise protocols . Booster sessions with study team members may also improve retention .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Adherence interventions that target multiple behavior change techniques have been suggested to improve compliance. Patient specific interventions to improve exercise motivation and reduce barriers to exercise may increase adherence to the exercise protocols . Booster sessions with study team members may also improve retention .…”
Section: Discussionmentioning
confidence: 95%
“…Patient specific interventions to improve exercise motivation and reduce barriers to exercise may increase adherence to the exercise protocols. 39 Booster sessions with study team members may also improve retention. 39 However, a strength of our study is that the intervention was implemented for both genders, including individuals within the age range most affected by OA and at different levels of physical functioning and pain, indicating that the typical individual affected by hip OA would experience similar outcomes as the individuals in this study.…”
Section: Discussionmentioning
confidence: 99%
“…For interventions to have an impact on outcomes beyond the several months of follow‐up generally reported in clinical trials, and to be effective in whole populations, wide access to interventions, as well as high adherence, are essential. Recent reviews have highlighted the need for identifying predictors of adherence to lifestyle interventions and barriers to behaviour change, with particular emphasis on the design and evaluation of interventions to improve adherence (Nicolson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although their impact is to be demonstrated, experts in OA and consumers have identified and prioritized 21 key messages for people with joint pain associated with OA, which may be used to inform the content of educational materials about important aspects of OA and its management (French et al, 2014). (Nicolson et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…While no single strategy will universally increase exercise adherence or reduce barriers to exercise for all patients, some emerging techniques have been explored. Evidence suggests that returning for further physiotherapy after an initial exercise period and promoting behavioural graded exercise (the self-regulation of gradual increases in exercise incorporated into activities of daily living) may be beneficial 19. It has been shown that group education can help achieve clinical benefits in individuals with hip and/or knee OA.…”
Section: Best Practice In Oa Management (Prevention and Treatment)mentioning
confidence: 99%